Crystal structure of human PNP complexed with hypoxanthine and sulfate ion - Canduri, F.; Fadel, V; Dias, MVB; Basso, L. A.; Palma, Mario Sergio [UNESP]; Santos, D. S.; de Azevedo, W. F. (Elsevier B.V., 2005)
Purine nucleoside phosphorylase (PNP) is a ubiquitous enzyme, which plays a key role in the purine salvage pathway, and PNP deficiency in humans leads to an impairment of T-cell function, usually with no apparent effects on B-cell function. Human PNP has been submitted to intensive structure-based design of inhibitors, most of them using low-resolution structures of human PNP. Here we report the crystal structure of human PNP in complex with hypoxanthine, refined to 2.6 Angstrom resolution. The intermolecular interaction between ligand and PNP is discussed. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: PNP; synchrotron radiation; Structure; drug design; hypoxanthine